1988
DOI: 10.1128/mcb.8.7.2933-2941.1988
|View full text |Cite
|
Sign up to set email alerts
|

Processing, Secretion, and Biological Properties of a Novel Growth Factor of the Fibroblast Growth Factor Family with Oncogenic Potential

Abstract: We recently reported that the protein encoded in a novel human oncogene isolated from Kaposi sarcoma DNA was a growth factor with significant homology to basic and acidic fibroblast growth factors (FGFs). To study the properties of this growth factor (referred to as K-FGF) and the mechanism by which the K-fgf oncogene transforms cells, we have studied the production and processing of K-FGF in COS-1 cells transfected with a plasmid encoding the K-fgf cDNA. The results show that, unlike basic and acidic FGFs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…FGF3-related products were readily detected in COS-1 cell lysates, but direct immunoblot analysis of the culture medium failed to detect any exported protein (15). In contrast, when COS-1 cells were transfected with Fgf-4 cDNA, substantial amounts of functional protein could be recovered from the culture fluid (12,21,53). Figure la and b illustrates these findings; in this experiment a combination of immunoprecipitation with specific antisera raised against the C-terminal peptides of mouse FGF3 and FGF4 and subsequent immunoblotting with the same sera were used.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…FGF3-related products were readily detected in COS-1 cell lysates, but direct immunoblot analysis of the culture medium failed to detect any exported protein (15). In contrast, when COS-1 cells were transfected with Fgf-4 cDNA, substantial amounts of functional protein could be recovered from the culture fluid (12,21,53). Figure la and b illustrates these findings; in this experiment a combination of immunoprecipitation with specific antisera raised against the C-terminal peptides of mouse FGF3 and FGF4 and subsequent immunoblotting with the same sera were used.…”
Section: Resultsmentioning
confidence: 93%
“…With FGF4, the major intracellular form is a 22-kDa protein, which, after processing and secondary glycosylation, appears in the culture medium as a series of products of around 21.5 to 23.5 kDa (Fig. lb) (12,21,53). Although these multiple extracellular forms of FGF4 have not been fully characterized, they may reflect 0-linked glycosylation, and it has been reported that the protein can undergo further processing at the amino terminus (36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such negative results were obtained by using different experimental protocols and different polyclonal antisera, so that the absence of immunoreactive material was unlikely to be attributable to a technical artifact or masking of epitopes. While it is conceivable that the secreted protein is very rapidly degraded or quantitatively sequestered in the extracellular matrix (ECM), other members of the FGF family behave more conventionally and can be detected in conditioned medium by immunological or functional assays (7,19,20,30,37). Since there is increasing evidence that FGFs transform cells via an extracellular autocrine loop (13,30), we felt that it was essential to reevaluate the secretion and subsequent fate of To facilitate these analyses, we focused on two clonal lines of NIH3T3 cells, designated DMI-1 and DMI-3, that produce high levels of Int-2 (14).…”
mentioning
confidence: 99%